Europe in the Seventies : aspects of recent art. - The Art Institute of Chicago; The Hirshorn Museum and Sculpture Garden Collection, Washington; San Francisco Museum of Modern Art, San Francisco; The Fort Worth Art Museum, Fort Worth; The Contemporary Arts Center, Cincinnati (Chicago : The Art Institute of Chicago, 1977)
Anselmo, Giovanni ; Becher, Bernd ; Becher, Hilla ; Broodthaers, Marcel ; Brouwn, Stanley ; Buren, Daniel ; Burgin, Victor ; Darboven, Hanne ; Defraoui, Cherif ; Dibbets, Jan ; Van Elk, Ger ; Fulton, Hamish ; Gilbert & George ; Le Gac, Jean ; Long, Richard ; etc.
Europe in the Seventies : aspects of recent art, The Art Institute of Chicago, October 8 - November 27, 1977 / The Hirshhorn Museum and Sculpture Garden Smithsonian Institution, Washington DC, March 16 - May 7, 1978 / The San Francisco Museum of Modern Art, San Francisco, June 23 - August 6, 1978 / The Forth Worth Art Museum, Fort Worth, Texas, September 24 - October 29, 1978 / The Contemporary Arts Center, Cincinnati, December 1, 1978 - January 31, 1979
boek